Interplay of personal, pet, and environmental colonization in households affected by community-associated methicillin-resistant Staphylococcus aureus. Issue 3 (March 2019) - Hogan, Patrick G.; Mork, Ryan L.; Boyle, Mary G.; Muenks, Carol E.; Morelli, John J.; Thompson, Ryley M.; Sullivan, Melanie L.; Gehlert, Sarah J.; Merlo, Jessica R.; McKenzie, Matt G.; Wardenburg, Juliane Bubeck; Rzhetsky, Andrey; et al.
Highlights: MRSA contaminated 46% of environments in households of children with MRSA SSTI. The most prevalent sites of MRSA were index case bed linens and TV remote control. Risk factors included household member MRSA colonization burden and home rental. 14% of pet dogs and cats were colonized with MRSA. The infecting strain type was the most common strain recovered from the environment. Abstract: Objective: We sought to determine the prevalence, molecular epidemiology, and factors associated with Staphylococcus aureus environmental surface and pet colonization in households of children with community-associated methicillin-resistant S. aureus (CA–MRSA) infection. Methods: Between 2012 and 2015, 150 children with CA–MRSA infections and their household contacts and pets were enrolled in this cross-sectional study in metropolitan Saint Louis, MO. Cultures to detect S. aureus were collected from 3 anatomic sites of household members, 2 dog/cat sites, and 21 environmental surfaces in each household. Molecular epidemiology of S. aureus isolates was determined via repetitive-sequence PCR. Generalized linear models were developed to identify factors associated with S. aureus /MRSA household contamination. Results: MRSA was recovered from environmental surfaces in 69 (46%) households (median 2 surfaces [range 1–18]). The enrollment infecting strain type was the most common strain recovered from the environment in most (64%) households. In generalized linear models, factors associated with a higher proportion of MRSA-contaminated environmental surfaces were household member MRSA colonization burden, MRSA as the dominant S. aureus strain colonizing household members, more strain types per household member, index case African–American race, and renting (vs. owning) the home. Of 132 pets, 14% were colonized with MRSA. Pets whose primary caretaker was MRSA-colonized were more likely to be MRSA-colonized than pets whose primary caretaker was not MRSA-colonized (50% vs. 4%, p < 0.001). Conclusions: Household environments and pet dogs and cats serve as reservoirs of MRSA. Household member MRSA colonization burden predicts environmental MRSA contamination. Longitudinal studies will inform the directionality of household transmission.